2012
DOI: 10.1007/s11103-011-9872-z
|View full text |Cite
|
Sign up to set email alerts
|

Survey of sugar beet (Beta vulgaris L.) hAT transposons and MITE-like hATpin derivatives

Abstract: Genome-wide analyses of repetitive DNA suggest a significant impact particularly of transposable elements on genome size and evolution of virtually all eukaryotic organisms. In this study, we analyzed the abundance and diversity of the hAT transposon superfamily of the sugar beet (B. vulgaris) genome, using molecular, bioinformatic and cytogenetic approaches. We identified 81 transposase-coding sequences, three of which are part of structurally intact but nonfunctional hAT transposons (BvhAT), in a B. vulgaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…which harbors 16 SINE copies . Therefore, we propose that DNA transposons and SINEs in sugar beet also influence gene expression in euchromatic generich regions (Menzel et al, 2006(Menzel et al, , 2012Schwichtenberg et al, 2016), because they might be targets for siRNAdirected CHH methylation. Accordingly, increased CHH methylation levels of small dispersed satellite DNA arrays (in the presence of corresponding 24-nucleotide siRNAs) in euchromatic regions hint at a functional role for small satellite arrays in gene silencing via CHH methylation .…”
Section: Asymmetric Chh Methylation Is Very Different Between Callus mentioning
confidence: 99%
See 1 more Smart Citation
“…which harbors 16 SINE copies . Therefore, we propose that DNA transposons and SINEs in sugar beet also influence gene expression in euchromatic generich regions (Menzel et al, 2006(Menzel et al, , 2012Schwichtenberg et al, 2016), because they might be targets for siRNAdirected CHH methylation. Accordingly, increased CHH methylation levels of small dispersed satellite DNA arrays (in the presence of corresponding 24-nucleotide siRNAs) in euchromatic regions hint at a functional role for small satellite arrays in gene silencing via CHH methylation .…”
Section: Asymmetric Chh Methylation Is Very Different Between Callus mentioning
confidence: 99%
“…Because repeats are fragmentarily included in the sugar beet reference genome, this bottleneck has recently been overcome by chromatin immunoprecipitation sequencing with antibodies against the sugar beet-specific centromeric variant of histone H3 and the dimethylation of lysine 9 of histone H3 (H3K9me2), uncovering the proportion of repetitive sequences in centromeric chromatin and non-centromeric heterochromatin (Kowar et al, 2016). Both regions are predominantly enriched with satellite DNA, long terminal repeat (LTR) retrotransposons and DNA transposons of different families and, thus far, a large number of these repeats have been described in detail (Schmidt and Heslop-Harrison, 1998;Weber and Schmidt, 2009;Wenke et al, 2009;Weber et al, 2010Weber et al, , 2013Zakrzewski et al, 2010Zakrzewski et al, , 2011Zakrzewski et al, , 2013Zakrzewski et al, , 2014Menzel et al, 2012;Wollrab et al, 2012;Heitkam et al, 2014;Schwichtenberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Transposable element contributes in plant gene regulation ( 53 ). Such transposable elements are present in sugarbeet also ( 54 ). It is probable that short sequence repeats in those locations are also involved in the regulation of gene expression ( 55 ).…”
Section: Utility Of the Databasementioning
confidence: 99%
“…The subtelomeric heterochromatic regions are characterized by the presence of the satellite family pAV [ 40 ]. Small dispersed heterochromatic spots consist of a variety of different repetitive elements including satellite DNAs, DNA transposons and LTR and Non-LTR retrotransposons [ 41 44 ]. In interphase nuclei it has been shown that sugar beet heterochromatin is characterized by the presence of H3K9me2.…”
Section: Introductionmentioning
confidence: 99%